A Novel Sterically Bulky Hole Transporter to Remarkably Improve the Lifetime of Thermally Activated Delayed Fluorescent OLEDs at High Brightness. Issue 18 (27th December 2017) - Kamata, Takahiro; Sasabe, Hisahiro; Igarashi, Masahiro; Kido, Junji
Abstract: For the practical application of organic light emitting devices (OLEDs) based on thermally activated delayed fluorescence (TADF) for large area TV and solid state lighting, low power consumption as well as the operation lifetime at high brightness over 1000 cd m −2 must be improved. Here, we have developed a novel hexaphenylbenzene‐based sterically bulky hole‐transport layer named 4DBTHPB with deep ionization potential of 5.8 eV and high triplet energy of 2.7 eV. By using 4DBTHPB, we can realize a highly efficient and stable TADF OLED exhibiting external quantum efficiency of 21.6 % and power efficiency of 54.3 lm W −1 and operation lifetime at 50 % (LT50 ) of approximately 10 000 h at an initial luminance of 1000 cd m −2 . These performances are comparable to those of the state‐of‐the‐art green phosphorescent OLEDs reported in the scientific literatures. Abstract : A highly efficient and stable TADF OLED exhibiting external quantum efficiency of 21.6 % and operation lifetime at 50 % of approximately 10 000 h at an initial luminance of 1000 cd m −2 is realized by using a novel sterically bulky hole transporter named 4DBTHPB. These performances are comparable to those of the state‐of‐the‐art green phosphorescent OLEDs reported in the scientific literatures.